The Effect of Manure Application to 3 years old of Teak (Tectona grandis. L. f) Growth in Intercropping Land - Gunawan Gunawan; Asep Rohandi (Balai Litbang Teknologi Agroforestry, Ciamis, 2019)
Planting system with one species continuously causes the degradation of land and the decline of plant productivity. It also occurs in teak (Tectona grandis L. f.) plantation. Application of manure in intercropping pattern was expected to improve the quality of the soil. This study aims to determine the effect of manure on 3 years old teak productivity and to develop of site management model in silvicultural practices to increase the teak plantation productivity. This study used a completely randomized block design with 8 treatments, 4 replications and 100 plants for each plot. . Tree spacing was 3 x 3 meters. The parameters observed were high and diameter of teak. Statistical analysis used was variance analysis at the 0.05 and 0.01 level test. It was continued by a tendency or trend test for the treatment. The results showed that the manure application 30 tons/ha with intercropping gave the most positive growth compared to other treatments. Meanwhile, intercropping provides better plant compared to non-intercropped plants.